Frailty Syndrome and Oxidative Stress as Possible Links Between Age-Related Hearing Loss and Alzheimer’s Disease - Alvarado, Juan Carlos; Fuentes-Santamaría, Verónica; Juiz, José M. (Frontiers in Neuroscience, 2022)
As it is well known, a worldwide improvement in life expectancy has taken place. This has brought an increase in chronic pathologies associated with aging. Cardiovascular, musculoskeletal, psychiatric, and neurodegenerative conditions are common in elderly subjects. As far as neurodegenerative diseases are concerned dementias and particularly, Alzheimer’s disease (AD) occupy a central epidemiological position given their high prevalence and their profound negative impact on the quality of life and life expectancy. The amyloid cascade hypothesis partly explains the immediate cause of AD. However, limited therapeutical success based on this hypothesis suggests more complex remote mechanisms underlying its genesis and development. For instance, the strong association of AD with another irreversible neurodegenerative pathology, without curative treatment and complex etiology such as presbycusis, reaffirms the intricate nature of the etiopathogenesis of AD. Recently, oxidative stress and frailty syndrome have been proposed, independently, as key factors underlying the onset and/or development of AD and presbycusis. Therefore, the present review summarizes recent findings about the etiology of the above-mentioned neurodegenerative diseases, providing a critical view of the possible interplay among oxidative stress, frailty syndrome, AD and presbycusis, that may help to unravel the common mechanisms shared by both pathologies. This knowledge would help to design new possible therapeutic strategies that in turn, will improve the quality of life of these patients.